Interoceptive hunger, eating attitudes and beliefs - Stevenson, Richard J.; Hill, Brayson J.; Hughes, Alannah; Wright, Madeline; Bartlett, Johanna; Saluja, Supreet; Francis, Heather M. (Frontiers in Psychology, 2023)
Interoceptive individual differences have garnered interest because of their relationship with mental health. One type of individual difference that has received little attention is variability in the sensation/s that are understood to mean a particular interoceptive state, something that may be especially relevant for hunger. We examined if interoceptive hunger is multidimensional and idiosyncratic, if it is reliable, and if it is linked to dysfunctional eating and beliefs about the causes of hunger. Participants completed a survey just before a main meal, with most retested around 1 month later. We found that interoceptive hunger has 11 dimensions, and while people differ considerably in their combinations of interoceptive hungers, these represent only 4% of all possible permutations. Hunger reports were reliable. We found relationships between variability in hunger interoception and dysfunctional eating, especially for uncontrolled eating. We also found that hunger beliefs were in some cases strongly related to aspects of hunger interoception. The implications of these findings are discussed.